Answer: - 84/3
Step-by-step explanation: hope this helps!
Answer:
<u>A = πR^2</u>
Step-by-step explanation:
<h3>Please refer to the attachment for explanation.</h3>
Answers:
Yes
Yes
No
Hope this helped :)
Answer:
(f of)(-2) = -65
Step-by-step explanation:
<u>Set up (f of)(-2)</u>
(f o f)(-2) = f(f(-2))
<u>Once you get (fof)(-2) you then have f(#)</u>
f(6(-2) + 1) = f(-11)
6(-11) + 1 = -66 + 1 = -65
Answer: $3.69
Step-by-step explanation:
Laura bought 4 1/3 bushels of apples.
Firs convert this to an improper fraction for easier calculation:
= 13/3 bushels of apples.
If cost $16 altogether, individually they must cost:
= Cost / Quantity purchased
= 16 ÷ 13/3
= 16 * 3/13
= $3.69
<em>Note: You can divide by a fraction by multiplying the inverse of that fraction. </em>